2016
DOI: 10.1016/j.ympev.2015.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Dating and biogeographical patterns in the sea slug genus Acanthodoris Gray, 1850 (Mollusca, Gastropoda, Nudibranchia)

Abstract: Recent studies investigating vicariance and dispersal have been focused on correlating major geological events with instances of taxonomic expansion by incorporating the fossil record with molecular clock analyses. However, this approach becomes problematic for soft-bodied organisms that are poorly represented in the fossil record. Here, we estimate the phylogenetic relationships of the nudibranch genus Acanthodoris Gray, 1850 using three molecular markers (16S, COI, H3), and then test two alternative geologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 63 publications
(75 reference statements)
0
11
0
Order By: Relevance
“…5). Although the p-distance between these species is relatively low, lowered level of divergence is a characteristic for sibling species that descent during Pleistocene glaciations (Breslau, Valdés & Chichvarkhin, in press; Lindsay et al, 2016; Klienberger et al, 2016; Hallas, Simison & Gosliner, 2016). Likely, this phenomenon also occurs in amphiboreal species with direct development, e.g., Cadlina (Thompson, 1967) whose speciation took place during recent dispersal from a refugia.…”
Section: Resultsmentioning
confidence: 99%
“…5). Although the p-distance between these species is relatively low, lowered level of divergence is a characteristic for sibling species that descent during Pleistocene glaciations (Breslau, Valdés & Chichvarkhin, in press; Lindsay et al, 2016; Klienberger et al, 2016; Hallas, Simison & Gosliner, 2016). Likely, this phenomenon also occurs in amphiboreal species with direct development, e.g., Cadlina (Thompson, 1967) whose speciation took place during recent dispersal from a refugia.…”
Section: Resultsmentioning
confidence: 99%
“…Most previous studies have assumed the simultaneous divergence of sister taxa, ignoring differences in their environmental tolerances, ecological requirements, dispersal ability, and disregarding that biogeographic events will impact different ecological groups at different times (De Baets et al 2016). For example, most studies have assumed that the divergence of trans-Bering sister taxa coincided with the first opening of the Bering Strait (e.g., Hrincevich et al 2000;Wares and Cunningham 2001;Foltz et al 2008;Gérard et al 2008;Hallas et al 2016), ignoring the fact that its repeated opening and closure meant that multiple pulses of trans-Bering migrations are likely, a conclusion supported by the data (Carr 2010;Loeza-Quintana and Adamowicz 2018). If one repeats the calibration process in molluscs assuming simultaneous divergence during the major trans-Arctic interchange, the calibrated rate estimate would vary between 0.5%/MY and 6.1%/MY, depending upon which pair(s) is selected.…”
Section: Molecular Evolutionary Rate For Northern Marine Invertebratesmentioning
confidence: 99%
“…After exploring alternative calibration scenarios, it was apparent that the iterative calibration approach yielded results most concordant with the geological history of the Bering Strait. For example, the use of Bayesian analysis to calibrate a clock for the sister pair of Acanthodoris (Mollusca) dated their divergence at 5.32 Ma with the first opening of the Bering Strait (Hallas et al 2016). However, the inclusion of an additional calibration based on formation of the Baja Peninsula resulted in reducing the divergence time estimate to 2.4 Ma, with both estimates differing from the divergence time (1.2-1.4 Ma) estimated in this study.…”
Section: Divergence Times For Northern Marine Invertebratesmentioning
confidence: 99%
“…() and Hallas et al. () also showed that the rockweed, Fucus , and the sea slug, Acanthodoris , respectively, could have invaded through the Bering Strait 3.5–5 mya.…”
mentioning
confidence: 94%